The Rhodanese PspE Converts Thiosulfate to Cellular Sulfane Sulfur in Escherichia coli - Qiaoli Yu; Mingxue Ran; Yuping Xin; Huaiwei Liu; Honglei Liu; Yongzhen Xia; Luying Xun (MDPI AG, 2023)
Hydrogen sulfide (H2S) and its oxidation product zero-valent sulfur (S0) play important roles in animals, plants, and bacteria. Inside cells, S0 exists in various forms, including polysulfide and persulfide, which are collectively referred to as sulfane sulfur. Due to the known health benefits, the donors of H2S and sulfane sulfur have been developed and tested. Among them, thiosulfate is a known H2S and sulfane sulfur donor. We have previously reported that thiosulfate is an effective sulfane sulfur donor in Escherichia coli; however, it is unclear how it converts thiosulfate to cellular sulfane sulfur. In this study, we showed that one of the various rhodaneses, PspE, in E. coli was responsible for the conversion. After the thiosulfate addition, the ΔpspE mutant did not increase cellular sulfane sulfur, but the wild type and the complemented strain ΔpspE::pspE increased cellular sulfane sulfur from about 92 μM to 220 μM and 355 μM, respectively. LC-MS analysis revealed a significant increase in glutathione persulfide (GSSH) in the wild type and the ΔpspE::pspE strain. The kinetic analysis supported that PspE was the most effective rhodanese in E. coli in converting thiosulfate to glutathione persulfide. The increased cellular sulfane sulfur alleviated the toxicity of hydrogen peroxide during E. coli growth. Although cellular thiols might reduce the increased cellular sulfane sulfur to H2S, increased H2S was not detected in the wild type. The finding that rhodanese is required to convert thiosulfate to cellular sulfane sulfur in E. coli may guide the use of thiosulfate as the donor of H2S and sulfane sulfur in human and animal tests.